2005
DOI: 10.1128/jvi.79.3.1452-1462.2005
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Rhesus Macaques with RecombinantMycobacterium bovisBacillus Calmette-Guérin Env V3 Elicits Neutralizing Antibody-Mediated Protection against Simian-Human Immunodeficiency Virus with a Homologous but Not a Heterologous V3 Motif

Abstract: Although the correlates of vaccine-induced protection against human immunodeficiency virus type 1 (HIV-1) are not fully known, it is presumed that neutralizing antibodies (NAb) play a role in controlling virus infection. In this study, we examined immune responses elicited in rhesus macaques following vaccination with recombinant Mycobacterium bovis bacillus Calmette-Guérin expressing an HIV-1 Env V3 antigen (rBCG Env V3). We also determined the effect of vaccination on protection against challenge with either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 57 publications
0
42
0
Order By: Relevance
“…In order to fully take advantage of the potential benefits of traditional live vectors in HIV-1 vaccine development, we studied the Mycobacterium bovis bacillus Calmette-Guérin (BCG) substrain Tokyo 172 (6) and the replication-deficient vaccinia virus vaccine strain DIs (22,50), both of which have been shown to be nonpathogenic when inoculated into immunodeficient animals (41,51,53) as live recombinant vaccine vehicles (1,(17)(18)(19)(46)(47)(48). As further evidence of the potential of the live vectors for use in HIV/AIDS vaccines, we noted that a recombinant M. bovis BCG vector candidate vaccine for HIV-1-induced positive immune responses in animals (17,46). Moreover, we found that recombinant vaccinia virus DIs encoding the simian immunodeficiency virus (SIV) gene was effective at eliciting anti-SIV immunity in mice when administered as a booster antigen after priming with SIV DNA (47).…”
mentioning
confidence: 99%
“…In order to fully take advantage of the potential benefits of traditional live vectors in HIV-1 vaccine development, we studied the Mycobacterium bovis bacillus Calmette-Guérin (BCG) substrain Tokyo 172 (6) and the replication-deficient vaccinia virus vaccine strain DIs (22,50), both of which have been shown to be nonpathogenic when inoculated into immunodeficient animals (41,51,53) as live recombinant vaccine vehicles (1,(17)(18)(19)(46)(47)(48). As further evidence of the potential of the live vectors for use in HIV/AIDS vaccines, we noted that a recombinant M. bovis BCG vector candidate vaccine for HIV-1-induced positive immune responses in animals (17,46). Moreover, we found that recombinant vaccinia virus DIs encoding the simian immunodeficiency virus (SIV) gene was effective at eliciting anti-SIV immunity in mice when administered as a booster antigen after priming with SIV DNA (47).…”
mentioning
confidence: 99%
“…However, the biological activity of Ab responsible for protection in vivo is unknown. Although neutralizing Ab activity often correlates with protection (3,5,8,9), nonneutralizing Abs also prevent or modulate SIV and SHIV infections, and the fact that Ab neutralizes cell-free virus in vitro does not necessarily implicate neutralization as the critical Ab function in vivo.…”
mentioning
confidence: 99%
“…SIV Gag-and SHIV Env-specific IgG Ab end-point titers of the macaques' sera were measured by ELISA as previously described (23,27,30 The SHIV Env-specific neutralization Ab responses induced by challenge with SHIV were analyzed as previously described (28). In brief, 10 g/ml purified macaque IgG was incubated with 100 50% tissue culture infectious doses (TCID 50 ) of SHIV-C2/1, then cultured in M8166 cells.…”
Section: Abs To Siv Gag P27 and Shiv 896p Envmentioning
confidence: 99%
“…The macaques were fed and cared for in accordance with the standard operating procedure approved by the Ministry of Education, Culture, Sports, Science, and Technology of Japan. The study was performed in the P3 facility under guidelines established by the laboratory biosafety manual of the World Health Organization (28).…”
Section: Animalsmentioning
confidence: 99%